Low Earth Orbit Satellite Design - Sebestyen, George; Fujikawa, Steve; Galassi, Nicholas; Chuchra, Alex.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
In recent decades, the number of satellites being built and launched into Earth's orbit has grown immensely, alongside the field of space engineering itself. This book offers an in-depth guide to engineers and professionals seeking to understand the technologies behind Low Earth Orbit satellites. With access to special spreadsheets that provide the key equations and relationships needed for mastering spacecraft design, this book gives the growing crop of space engineers and professionals the tools and resources they need to prepare their own LEO satellite designs, which is especially useful for designers of small satellites such as those launched by universities. Each chapter breaks down the various mathematics and principles underlying current spacecraft software and hardware designs. .
Preface -- About the Authors -- Chapter 1: Introduction -- Chapter 2: The Space Environment -- Chapter 3: Satellite Missions -- Chapter 4: Orbits and Space-Related Geometry -- Chapter 5: Electric Power Subsystem Design -- Chapter 6: Spacecraft Communications -- Chapter 7: Spacecraft Digital Hardware -- Chapter 8: Attitude Determination and Control Subsystem (ADACS) -- Chapter 9: Spacecraft Software -- Chapter 10: Spacecraft Structure -- Chapter 11: Deployment Mechanisms -- Chapter 12: Propulsion -- Chapter 13: Thermal Design -- Chapter 14: Radiation Hardening, Reliability and Redundancy -- Chapter 15: Integration and Test -- Chapter 16: Launch Vehicles and the Spacecraft Interfaces -- Chapter 17: Ground Stations and Ground Support Equipment -- Chapter 18: Spacecraft Operations -- Chapter 19: Low Cost Design and Development -- Chapter 20: Systems Engineering and Program Management -- Chapter 21: A Spacecraft Design Example -- Chapter 22: Downloadable Spreadsheets -- Appendix 1 -- Appendix 2 -- Appendix 3 -- Appendix 4 -- Appendix 5 -- Appendix 6 -- Appendix 7 -- Appendix 8 -- References -- Glossary -- Index.
Keywords: Aerospace engineering; Astronautics; Solar system; Software engineering; Aerospace Technology and Astronautics; Space Physics; Software Engineering